Effects of online reading strategies and learning styles on reading comprehension of Malaysian tertiary ESL learners - Chiam, Kee Swan (2015)
Many Malaysian learners struggle at the tertiary level due to poor reading skills (Majid, Jelas, & Azman, 2006; Ramaiah, 1997; Ellis, 1996 and Ramaiah & Nambiar, 1993). While it is hard to address core problems such as low English proficiency, some researchers believe that reading comprehension can be improved significantly through reading strategy instruction (Sorrell, 1996; Fehrenbach, 1991). However, different learners respond to reading strategies differently (Hsieh, 2007; Sharma & Hannafin, 2004). There is a lack of research addressing the congruence between reading strategy and differences between learners which has served as the impetus for the present research. The purpose of this study was to discover the relative effectiveness of different types of reading strategies on measures of reading comprehension performance for students with different learning styles. Students were separated into four learning style groups (active, sensitive, visual and sequential) based on their scores on the Index of Learning Styles (ILS) questionnaire developed by Felder and Solomon (2003). A large sample was canvassed with the ILS to find learners with specific learning styles as stipulated by the research protocol. Since learners with only one learning style preference are rare, the final sample sizes comprised groups of 32-34 students. As such the repeated measures design was used to ensure mitigate the loss of power in the study. To reduce the sequencing effects that come with using a repeated measures design, counterbalancing was employed. The reading strategies were incorporated into the text and the different groups were made to answer a series of multiple choice questions to test their reading comprehension. A split-plot ANOVA was used to analyze the data collected. The results indicated that students with varying learning styles responded differently to the reading strategies tested in the study. Active learners performed better than other groups when using the keyword and question and answer strategy but performed significantly worse than other groups with the rereading strategy. Sensitive and sequential learners on the other hand performed better than other groups with the rereading strategy. Visual learners did well with the keyword strategy. Of the strategies tested, only the keyword strategy showed consistently positive results for all learning style groups. Each group scored higher on the keyword condition than on the control condition. Hence use of the keyword strategy is highly recommended in classroom environments and incorporating the keywords into texts to make texts easier to understand is a viable method for improving comprehension. The question and answer strategy should be used with caution as it results in sub-par comprehension for learning styles other than the active learning style. Similarly the rereading strategy which works well for sensitive and sequential learners should also be used only for these learners as it confuses active learners. In a nutshell, a student’s learning preference will influence the way information is processed and thus selecting and using appropriate reading strategies is essential to ensure the best possible results.